การสร้างสรรค์รายการโทรทัศน์ และการรับรู้ความหมายของผู้ชมรายการภัตตาคารบ้านทุ่ง - พาฝัน รงศิริกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
The Research focuses on surveying how the program’s meanings are constructed, transmitted and lastly perceived by the audience. The research is divided into 2 parts according to its purposes: first to study the creation of Phatta-Kharn-Ban-Tung TV program and the meanings transmitted toward the audience by applying textual analysis on the program, and applying the in-depth interview to the TV producers; secondly to study the meaning decoded by the audience, using focus group on a sampling of viewers. The result of the research indicates that the program emphasizes on " the beauty and the preciousness of rural living". The meaning is constructed through the use of narratives and images of "food" and "raw material" in rural areas. After studying the program, it is found that the first 4 meanings found most often in the program consist of: ‘The rural living is serene, simple, and related to nature.’ ‘Thai culture and rural wisdom is priceless’ ‘Perseverance, self-reliance and communal cooperation leads to success and happiness’ and ‘Our rural hometown is filled with warmth care and happiness’; secondly, ‘Thailand possesses an abundant supply of useful natural resources for its people’ ; and least of all ‘Organic farming and integrated farming system encourage healthy and sustainable life’ The audience’s messages most frequently decoded are: ‘The rural living.’, ‘Our rural hometown’ and ‘Thai culture and rural wisdom’; least of all ‘Thailand ‘s natural resources’. In conclusion, the program intends to promote cultural transmission among Thai people as well as to create a strong attachment toward their hometown, through the representation of ‘food’ and ‘rural living’